Developing a Latino Mentoring Program: Project MALES (Mentoring to Achieve Latino Educational Success). Issue 171 (3rd September 2015) - Sáenz, Victor B.; Ponjuan, Luis; Segovia, Jorge; Del Real Viramontes, José
Abstract : This chapter highlights the development of Project MALES (Mentoring to Achieve Latino Educational Success). At the center of Project MALES is a mentoring program that aims to cultivate an engaged support network for males of color at the University of Texas at Austin and across surrounding communities. Specifically, there is a discussion of the theories and framework that guided the creation of this mentoring program and its ongoing development.